2015
DOI: 10.1073/pnas.1423854112
|View full text |Cite
|
Sign up to set email alerts
|

Identifying personal microbiomes using metagenomic codes

Abstract: Community composition within the human microbiome varies across individuals, but it remains unknown if this variation is sufficient to uniquely identify individuals within large populations or stable enough to identify them over time. We investigated this by developing a hitting set-based coding algorithm and applying it to the Human Microbiome Project population. Our approach defined body site-specific metagenomic codes: sets of microbial taxa or genes prioritized to uniquely and stably identify individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
309
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(340 citation statements)
references
References 37 publications
24
309
2
5
Order By: Relevance
“…The unused single-end reads were combined with the unmapped reads and cd-hit-dup from the CD-HIT software suite 63 was used to remove duplicate reads. Velvet was then run over a range of k-mer sizes (27,31,35,39,43,47,51,55,59,63) with the IDBA-UD contigs as long read input (velveth parameters: -long contig.fa, velvetg parameter: -conserveLong yes). Afterwards, all newly assembled contig sequences from the different k-mer runs and the original IDBA-UD contigs were concatenated and clustered using cd-hit from the CD-HIT software suite (parameter: -c 0.99) to remove redundancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unused single-end reads were combined with the unmapped reads and cd-hit-dup from the CD-HIT software suite 63 was used to remove duplicate reads. Velvet was then run over a range of k-mer sizes (27,31,35,39,43,47,51,55,59,63) with the IDBA-UD contigs as long read input (velveth parameters: -long contig.fa, velvetg parameter: -conserveLong yes). Afterwards, all newly assembled contig sequences from the different k-mer runs and the original IDBA-UD contigs were concatenated and clustered using cd-hit from the CD-HIT software suite (parameter: -c 0.99) to remove redundancy.…”
Section: Methodsmentioning
confidence: 99%
“…The microbial consortia of the gut are known to be among the most stable human-associated microbial communities 2 , and sample donors remain identifiable from these based on metagenomic data when compared to data sets from earlier samples 39 . We investigated whether the patterns of individuality are also discernible on the other omic levels.…”
Section: Individuality Of Gut Microbiota On All Omic Levelsmentioning
confidence: 99%
“…We obtained IRB approval for both the use of student microbiome samples and the students' participation in educational research. We note that while human microbiome data are often not considered to be specific to a person, recent publications have demonstrated that microbiomes may be used to uniquely identify individuals (Franzosa et al 2015;.…”
Section: Topic Selection and Personal Samplesmentioning
confidence: 99%
“…The finding 1 , published in Proceedings of the National Academy of Sciences on 11 May, suggests that it might be possible to identify a participant in an anonymous study of the body's microbial denizens -its microbiome -and to reveal details about that person's health, diet or ethnicity. A publicly available trove of microbiome DNA maintained by the US National Institutes of Health (NIH), meanwhile, already contains potentially identifiable human DNA, according to a study 2 published in Genome Research on 29 April.…”
mentioning
confidence: 99%
“…"Right now, it's a little bit of a Wild West as far as microbiome data management goes," says Curtis Huttenhower, a computational biologist at the Harvard T. H. Chan School of Public Health in Boston, Massachusetts, who led the latest study 1 . "As the field develops, we need to make sure there's a realization that our microbiomes are highly unique.…”
mentioning
confidence: 99%